2021
DOI: 10.1021/acs.jmedchem.1c00065
|View full text |Cite
|
Sign up to set email alerts
|

From High-Throughput Screening to Target Validation: Benzo[d]isothiazoles as Potent and Selective Agonists of Human Transient Receptor Potential Cation Channel Subfamily M Member 5 Possessing In Vivo Gastrointestinal Prokinetic Activity in Rodents

Abstract: Transient receptor potential cation channel subfamily M member 5 (TRPM5) is a nonselective monovalent cation channel activated by intracellular Ca2+ increase. Within the gastrointestinal system, TRPM5 is expressed in the stoma, small intestine, and colon. In the search for a selective agonist of TRPM5 possessing in vivo gastrointestinal prokinetic activity, a high-throughput screening was performed and compound 1 was identified as a promising hit. Hit validation and hit to lead activities led to the discovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In human colonic cancer cells (HT29-18N2), TRPM5 channels have the potential as pharmacological targets for managing mucus-associated pathologies, such as cystic fibrosis [46], given their roles in regulating Ca 2+mediated mucin 2 and MUC5AC secretion [47]. TRPM5 agonists have shown promise in promoting rodent gastrointestinal prokinetic activity [48]. High TRPM5 mRNA expression has been associated with poor OS in both gastric cancer and melanoma patients [49].…”
Section: Discussionmentioning
confidence: 99%
“…In human colonic cancer cells (HT29-18N2), TRPM5 channels have the potential as pharmacological targets for managing mucus-associated pathologies, such as cystic fibrosis [46], given their roles in regulating Ca 2+mediated mucin 2 and MUC5AC secretion [47]. TRPM5 agonists have shown promise in promoting rodent gastrointestinal prokinetic activity [48]. High TRPM5 mRNA expression has been associated with poor OS in both gastric cancer and melanoma patients [49].…”
Section: Discussionmentioning
confidence: 99%
“…3 ) and that represent novel chemical matter to be utilized as starting points for hit-to-lead activities. Several potential hit series were identified, the hits were then clustered and further prioritized based on the calculated properties to give 16 chemical series, which were further explored by confirming the activity from solid samples and performing structure-activity relationship (SAR) expansion as recently described in Barilli et al [26] . Improved potency, selectivity and DMPK profiles would allow their use as in vitro and in vivo tool compounds to better understand the physiological and pathological roles of TRPM5 channels.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we tried a chemogenetic approach with Gq-or Gi-coupled receptors that respond only to synthetic ligands (DREADDs) 59 Finally, we decided to stimulate TRPM5 directly, since all tuft cell chemosensing pathways identified to date converge on TRPM5. We acquired a TRPM5 agonist compound called Class 8 (C8), 61,62 and found that it induced ion flux in both the pSI and dSI when administered lumenally or basolaterally, with a trend toward higher basolateral responses (Fig. 2K, S2P-Q).…”
Section: A Trpm5 Agonist Induces Tuft-and Ach-dependent Fluid Secreti...mentioning
confidence: 99%